Perceptions, precautions, and vaccine acceptance related to monkeypox in the public in China: A cross-sectional survey. Issue 2 (February 2023) - Wang, Bingyi; Peng, Xin; Li, Yuwei; Fu, Leiwen; Tian, Tian; Liang, Bingyu; Sun, Yinghui; Chen, Yuanyi; Wu, Xinsheng; Liu, Qi; Lin, Yi-Fan; Meng, Xiaojun; et al.
Abstract: Background: The World Health Organization declared monkeypox as a Public Health Emergency of International Concern. A cross-sectional online survey was conducted to understand beliefs, attitudes, perceived preventive measures, and vaccination acceptance related to monkeypox in the public in China. Methods: Between August 30 and September 15, 2022, we recruited adults through an online survey platform. Demographic characteristics, perceptions, common knowledge, concerns, attitudes, willingness to adopt preventive measures (including hygiene practices, social distancing, and travel avoidance), and vaccination acceptance related to monkeypox were collected. Logistic regression was used to assess correlates of concerns about monkeypox, willingness to adopt preventive measures, and vaccination acceptance. Results: 2135 participants were recruited (median age: 31.4 years). 62.7% were concerned about monkeypox. 33.2% were more concerned about monkeypox compared to COVID-19. Males (aOR 0.61, 95%CI 0.50–0.74), accessing monkeypox information from the Internet (0.77, 0.61–0.98), and willingness to adopt monkeypox vaccine (2.9, 2.38–3.53) were associated with concerns about monkeypox. Most participants were willing to adopt precautions (76.3% hygiene practices, 68.2% social distancing, 85.9% travel avoidance). Individuals who were concerned about monkeypox (hygiene practices: 2.09, 1.69–2.59; social distancing: 1.78, 1.46–2.16; travel avoidance: 1.74, 1.34–2.26) and had better knowledge about monkeypox (hygiene practices: 1.85, 1.48–2.31; social distancing: 2.17, 1.77–2.66; travel avoidance: 1.74, 1.34–2.26) were more likely to adopt precautions. 68.8% were willing to adopt monkeypox vaccine. Participants with older age (aged 40–49: 0.57, 0.38–0.85; aged 50 +: 0.50, 0.31–0.81), and higher income (¥6000–10, 000: 0.61, 0.39–0.95; ≥¥10, 000: 0.48, 0.30–0.77) were less likely to adopt the monkeypox vaccine. Being concerned more about monkeypox compared to COVID-19 (1.63, 1.31–2.02), and having better knowledge about monkeypox (1.34, 1.09–1.66) were associated with willingness to adopt vaccination. Conclusions: Compared with COVID-19, monkeypox attracted significantly less attention in the public in China, who currently have insufficient monkeypox knowledge. Interventions aimed at improving monkeypox knowledge and precautions among different groups of individuals in China are needed. Graphical Abstract: ga1